What can autopsy say about COVID-19? A case series of 60 autopsies. (May 2023) - Grassi, Simone; Arena, Vincenzo; Zedda, Massimo; Cazzato, Francesca; Cianci, Rossella; Gambassi, Giovanni; Oliva, Antonio
Highlights: The main aim of the COVID-19 autopsies is to distinguish patients who died with SARS-CoV-2 infection from those who died of COVID-19. The histopathological examination of the heart showed myocardiosclerosis in 73% cadavers. There is a clear relationship between SARS-CoV-2 and direct renal tubular damage responsible for AKI. Abstract: Introduction: Autopsies in SARS-CoV-2 infected cadavers are mainly performed to distinguish patients who died with SARS-CoV-2 infection from those who died of COVID-19. The aim of the current study is to assess the most frequent autopsy findings in patients who died of COVID-19 and to establish an association with clinical records. Materials and methods: 60 patients died between April 2020 and March 2021 after SARS-CoV-2 infection underwent a full autopsy performed at Fondazione Policlinico Universitario Agostino Gemelli IRCCS (Rome). Ante-mortem diagnosis of SARS-CoV-2 infection was microbiologically confirmed. Results: 55 (92%) of cases had at least a comorbidity. At microscopic examination, 40 (67%) of the patients presented pulmonary intravascular coagulation with an inflammatory pattern. Pulmonary microangiopathy was a rare finding (n = 8; 13%). Myocardiosclerosis was the main heart finding (n = 44; 73%). Liver involvement with congestion and hypotrophy was found in 33 (55%) of cadavers. Renal tubular epithelial exfoliation (n = 12; 20%) and intravascular coagulation (n = 4; 7%) were frequent observations. During hospitalization 31% of patients (n = 19) developed acute kidney injury (AKI). Conclusions: Lungs and kidneys have been shown to play a pivotal role in COVID-19. The gradual worsening of renal function and AKI might be the result of the progressive collapse of cardiopulmonary system.